2017
DOI: 10.1590/2237-6089-2016-0072
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in females with depression: a cross-sectional study

Abstract: The study showed a high prevalence of FSD in depressed females regardless of type and severity of depression. Depression with medical comorbidities was associated with a significant decrease in desire. Patients who expressed passive death wishes showed improved sexual function and significantly better orgasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 12 publications
2
19
0
4
Order By: Relevance
“…Furthermore, in this study, there was no relationship between age, socioeconomic situation, occupation, and sexual function. [ 21 ] Another study of Spanish women showed that according to the regression model there was an inverse correlation between sexual function and depression. In addition, there was a positive relation between education and sexual function and a negative correlation between sexual function and age.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this study, there was no relationship between age, socioeconomic situation, occupation, and sexual function. [ 21 ] Another study of Spanish women showed that according to the regression model there was an inverse correlation between sexual function and depression. In addition, there was a positive relation between education and sexual function and a negative correlation between sexual function and age.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a high prevalence of female sexual dysfunction in depressed women, regardless of type and severity of depression (25,37). Sexual dysfunction occurs at any stage of the sexual response cycle and reduces the quality of life of many women.…”
Section: Table 5 the Correlation Between The Scores Of Different Dommentioning
confidence: 99%
“…Mental disorders such as anxiety may reduce lubrication and clitoral vascular congestion and result in reduction of sexual arousal [ 34 ]. Also women with depression experience more sexual dysfunction [ 35 ]. Reduced sleep quality may be a cause of sleepiness during the day [ 36 ], which may result in accidents, decreased attention, alertness, and concentration, and reduced sexual drive [ 37 ].…”
Section: Discussionmentioning
confidence: 99%